Proposta pedagógica para o ensino do empreendedorismo nos cursos de graduação nos cursos de graduação em enfermagem - AMARAL, Thaiyza Mirela Oliveira (2020)
Considering the research question: how to introduce the teaching of Entrepreneurship in Nursing? This study aims to build a pedagogical proposal for the introduction of Entrepreneurship teaching to undergraduate nursing students. This is a qualitative and quantitative study based on the Delphi method, in which e-Delphi was used. The study is done in four rounds, the first qualitative and the others quantitative. The sample type of this study is named as Snowball, and nine teachers participated in the rounds. As results, the following variables reached consensus: understanding what is entrepreneurship; aspects of entrepreneurship; entrepreneurial skills; characteristics of the entrepreneurial nurse; ways to foster entrepreneurial skills; teaching experience; impact of context on entrepreneurship education; challenges of teaching in the area; period of entrepreneurship education within the courses; strategies for inserting entrepreneurship education; character of entrepreneurship disciplines. ideal number of subjects; ideal workload; active methodologies for teaching entrepreneurship; character of research and extension projects; extension project activities and research project themes. It is concluded that the study achieved its objective and was relevant due to its contribution to the theme, which is still limited in Brazil, compared to other countries. The number of participants and their permanence during the rounds was a limiting factor of the study. In addition, the results show that the competences and characteristics do not dialogue with each other, that is, what is understood to be important competences to be worked on by students has no relation with the profile pointed out as the ideal for the successful entrepreneurial nurse. labor market. Thus, it is possible to envisage for a next study to involve nurses who have experiences in enterprises, in order to identify and understand which factors were fundamental and which made it possible to undertake in nursing.